A filamentous cytoskeleton in vertebrate smooth muscle fibers (The Rockefeller University Press, 1976)
There are three classes of myofilaments in vertebrate smooth muscle fibers. The thin filaments correspond to actin and the thick filaments are identified with myosin. The third class of myofilaments (100 A diam) is distinguished from both the actin and the myosin on the basis of fine structure, solubility, and pattern of localization in the muscle fibers. Direct structural evidence is presented to show that the 100A filament constitute an integrated filamentous network with the dense bodies in the sarcoplasm, and that they are not connected to either the actin or myosin filaments. Examination of (a) isolated dense bodies, (b) series of consecutive sections through the dense bodies, and (c) redistributed dense bodies in stretched muscle fibers supports this conclusion. It follows that the 100-A filaments complexes constitute a structrally distinct filamentous network. Analysis of polyacrylamide gels after electrophoresis of cell fractions that are enriched with respect to the 100-A filaments shows the presence of a new muscle protein with a molecular weight of 55,000. This protein can form filamentous segments that closely resemble in structure the native, isolated 100-A filaments. The results indicate that the filamentous network has a structure and composition that distinguish it from the actin and myosin in vertebrate smooth muscle.